Trans-foramen ovale biopsy of a parasellar lesion guided by intraoperative CT neuronavigation with MRI fusion: A case report. (December 2014) - Lin, Martin Hsiu-Chu; Lee, Ming-Hsueh; Chen, Kuo-Tai; Lee, Tao-Chen; Cheng, Wan-Chun; Wang, Ting-Chun; Yang, Jen-Tsung
Abstract A 23-year-old male presented with a parasellar lesion which was suspected as disseminated intracranial germ cell tumour. The diagnosis of germinoma was made using immunohistochemistry from percutaneous trans-foramen ovale biopsy. This report describes the role of neuronavigation-guided biopsy through the foramen ovale for lesions in the parasellar region.